Drosophila TRAP230/240 are essential coactivators for Atonal in retinal neurogenesis. - Lim, J.; Lee, O.K.; Hsu, Y.C.; Singh, A.; Choi, K.W. (Developmental Biology, 2007)
The TRAP (thyroid hormone receptor associated proteins)/Mediator complex serves as a transcriptional coactivator. In Drosophila, Kohtalo (Kto) and Skuld (Skd), homologs of TRAP subunits, TRAP230 and TRAP240, respectively, are necessary for eye development. However, the transcriptional activators that require Kto and Skd have not been identified. Here we provide evidence that Kto and Skd are essential for the function of transcription factor Atonal (Ato) in spatial patterning of proneural clusters in the morphogenetic furrow. In the absence of Kto/Skd, Ato fails to induce its inhibitory target events such as EGFR signaling and Scabrous expression that result in ectopic Ato expression in the space between proneural groups. Kto/Skd are also required for positive Ato functions to induce Ato targets such as Ato itself and Senseless within the proneural clusters. We also show that Skd forms a protein complex with Ato in vivo. These data suggest that Kto/Skd act as essential coactivators for Ato expression during early retinal neurogenesis.